Empowering the Practice-Based Mentoring in Microteaching on Pre-Service ICT Teachers: High and Low Self-Efficacy Analysis - Husni Mubarok; Yossiri Yossatorn; Hirnanda Dimas Pradana; Syaiputra Wahyuda Meisa Diningrat; Arqoma Nurveda Carreza; Favian Avila Syahmi (Mitra Edukasi dan Publikasi, 2026)
Practice-based microteaching is now an important method in pre-service teacher education, particularly in ICT, as it creates a forum to practice teaching skills in a structured setting. However, the success of this depends greatly on the quality of guidance, which has the capacity to deliver timely and critical feedback. Self-efficacy, being the belief that an individual is capable of completing tasks, has been a significant predictor of learning achievement and motivation. The present research aims to examine the pre-service ICT teachers' learning achievement and the learning motivation of high and low self-efficacy individuals within a practice-based microteaching environment supported by mentoring. In experimental design, the subjects (N = 82) were divided into high and low self-efficacy according to a standardized self-efficacy scale. The data analysis in this study employed the t-test and Analysis of Covariance (ANCOVA). The findings of this study indicated there was no difference in learning achievement between the two groups on practice-based mentoring in microteaching for pre-service ICT teachers. Moreover, in intrinsic motivation, it was found that high self-efficacy practice-based mentoring microteaching students have significantly higher intrinsic motivation than low self-efficacy students. In the present study, however, low self-efficacy students for practice-based mentoring microteaching show significantly greater extrinsic motivation than high self-efficacy students. This research offers additional reference to scholars, teachers, and policymakers in investigating the role of self-efficacy in learning activity, learners' accomplishment in learning, and to supporting SDGs 4 and 5 in promoting the quality of education as well as gender equality.